The HIPC Initiative True and False Promises - Cohen, Daniel (OECD Publishing, 2000)
The paper develops the view that the perspective on the HIPC initiative is distorted by the fact that -contrary to the Brady deal itself- it lacks all perspective on the "market value" of the debt which is written down. The appropriate "market value" is one that takes account of the risk of non-payment: arrears, rescheduling and "constrained" refinancing of various sorts. Building upon econometric evidence that relies on middle income debtors in the eighties, the paper argues that the initiative is about ten times less generous than face value accounting would suggest ...
Keywords: Development